Opinions of customers of local government cultural services regarding the reconstruction of the Radziwiłł Castle and Park Complex in Biała Podlaska - Agnieszka Kuś; Danuta Guzal-Dec (Rozprawy Społeczne)
Abstract The aim of this paper is to examine the opinions of customers of local government cultural services on the need to revitalization the Radziwiłł Castle and Park Complex in Biała Podlaska and to identify determinants of these opinions.